ANALISIS PENGETAHUAN DAN SIKAP WISATAWAN TERHADAP POTENSI BENCANA DI DESTINASI WISATA DESA RINDU HATI KABUPATEN BENGKULU TENGAH - Munandar, Aries; Widiastuti, Wahyu (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
Bengkulu Province has many potential tourism objects, but Bengkulu Province is also a disaster-prone area, so that tourist objects will automatically become disaster-prone tourist objects. Several forms of natural events that can be a threat to disasters for tourist attraction areas are earthquakes, tsunamis, landslides, flash floods, hurricanes and tidal waves (Munandar, 2015). To reduce casualties, visitors should know the threat of disasters that could potentially occur in a tourist spot. The research question is: